PEMBERDAYAAN KELOMPOK GURU DALAM MENGEMBANGKAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA BERBASIS ETNOREALISTIK - Domu, Ichdar; Regar, Vivian Eleonara; Manangin, Susi Aryani; Mangelep, Navel Oktaviandy (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
The development of Pancasila Student Profiles in Indonesia must be carried out from an early age. This needs to be done simultaneously with the help of teachers and parents as the spearheads in learning in the classroom and at home. This community service activity focuses on empowering teachers to develop projects to strengthen Pancasila student profiles based on ethnorealistic. Ethnorealism was chosen because it is suitable for learning in early childhood and is close to the context of local wisdom that is close to students. The implementation of this service uses the methods of socialization, training, application of technology, mentoring evaluation, and program sustainability. The results obtained include the development of ethnorealistic-based educational props as a learning medium, especially in developing projects to strengthen Pancasila student profiles at Menara Perlindungan Kindergarten. In addition, teachers at the Mitra School (Tower Protection Kindergarten) can develop projects to strengthen Pancasila student profiles based on ethnorealism. Then, in this service, there is also an increase in Pancasila values ​​in students' personalities through the learning activities that have been carried out